A contribuição da ludicidade no desenvolvimento das crianças da educação infantil - MIRANDA, Iana da Cruz (2022)
The present work of conclusion of course entitled: The contribution of playfulness in the development of children of Early Childhood Education. In which we will have as thematic issues involving the development of the child, early childhood education and playfulness. For according to Zanluchi (2005), it is through playfulness that the child is prepared for the journey of life, maintaining relationships with the social context around him, systematizing with everyday situations. Thus, the problem that guides this study, is in how is the playfulness in the development of children of early childhood education? This study has as general objective to analyze the contribution of playfulness in the development of children’s early childhood education; as well as more specifically to recognize the contributions of play to the development of the child and analyze the playfulness in the practice of teachers of Early Childhood Education. Thus, a bibliographic survey was carried out, based on authors who make studies on the subject. This study also fits in a Qualitative Research, adopting as a data collection procedure a questionnaire with open questions for educators of Early Childhood Education, through a field research in an institution of Early Childhood Education of Abaetetuba/ PA. Thus, it can be concluded that the child develops fully through playfulness, through the strategies adopted in the educational context of early childhood education.